The Practice of Ideological State Apparatuses in Lois Lowry's The Giver (NOBEL: Journal of Literature and Language Teaching, 2017)
This article attempts to portray how a contemporary young adult literature entitled The Giver (Lowry, 1993) illustrates the operation of state apparatus in a dystopian setting of time and place. Applying Althusser's theory of state apparatuses, the study particularly focuses on a prominent issue of Ideological State Apparatuses (ISA) which is operated within The Giver's society. Descriptive qualitative research is applied to interpret the data in the novel. The result of this study reveals that the novel draws ISA as a tool to control and to maintain the dominance in this dystopian community. The ISA operates through training system, particular rule of language used by the community, media censorship, and family's role.